The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1002/nop2.1265
|View full text |Cite
|
Sign up to set email alerts
|

Foot self‐care behaviour in type 2 diabetes adults with and without comorbid heart failure

Abstract: Aims To compare the correlates of foot self‐care behaviours among type 2 diabetes mellitus (T2D) adults with and without comorbid heart failure (HF). Design Cross‐sectional, correlational, comparative design. Methods A 210 T2D adults (105 with HF and 105 without HF) participated from August–December 2020. Foot self‐care behaviour was measured using the foot care subscale of the Summary of Diabetes Self‐Care Activities (SDSCA) instrument. A st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 119 publications
3
2
1
Order By: Relevance
“…This is similar to previous studies which linked low household income with poor self‐care behaviors in PwD. 39 , 40 People experiencing economic insecurity are more likely to be diagnosed with Type 2 diabetes and experience serious health complications. 41 Additionally, it is well‐documented that adherence to diabetes self‐care practices, in general, is significantly lower among socio‐economically disadvantaged PwD.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…This is similar to previous studies which linked low household income with poor self‐care behaviors in PwD. 39 , 40 People experiencing economic insecurity are more likely to be diagnosed with Type 2 diabetes and experience serious health complications. 41 Additionally, it is well‐documented that adherence to diabetes self‐care practices, in general, is significantly lower among socio‐economically disadvantaged PwD.…”
Section: Discussionsupporting
confidence: 90%
“…Monthly household income independently predicted improved adherence to FSC practices. This is similar to previous studies which linked low household income with poor self‐care behaviors in PwD 39,40 . People experiencing economic insecurity are more likely to be diagnosed with Type 2 diabetes and experience serious health complications 41 .…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Previous investigations found conditions such as retinopathy, heart failure, and PAD as predictors of higher adherence and foot self-care among people with diabetesrelated foot disease. [42][43][44] However, we found that all the above variables were not associated significantly with the overall foot self-care in our study. Last, participants from the KAUH were potentially exposed to further empowerment or engagement to perform the needed foot self-care, which could have been another plausible explanation.…”
Section: Discussioncontrasting
confidence: 86%